Quadrupole Last‐Passage Algorithm for Charge Density on an L‐Shaped Conducting Surface. Issue 1 (7th August 2021) - Jang, Hoseung; Park, Jongmin; Yu, Unjong; Hwang, Chi‐Ok
Abstract: The last‐passage (LP) Monte Carlo algorithms for the charge density on an L‐shaped conducting surface are further developed by deriving a quadrupole LP Green's function on the L‐shaped flat surface. To demonstrate the algorithm, charge densities on an L‐shaped conductor are computed in 3D space and it is found that these results agree very well with the ones from the Given‐Hwang's original last‐passage algorithm on a flat surface. Compared with the Given‐Hwang's LP algorithm, the quadrupole LP one is very suitable for charge density near the L‐shaped edge boundary. Abstract : The last‐passage (LP) Monte Carlo algorithms for the charge density on an L‐shaped conducting surface is further developed. To demonstrate the algorithm, charge densities on an L‐shaped conductor is computed in 3D space. Compared with the previous Given‐Hwang's LP algorithm, the quadrupole LP one is very suitable for charge density near the L‐shaped edge boundary.